Pendidikan Kesehatan untuk Meningkatkan Kesiapan Ibu Menghadapi Menopause - Veronica Silalahi; Marcellina Rasemi Widayanti; Agung Kurniawan Saputra (Jurnal Abdimas Kesehatan (JAK), 2026)
Menopause is a natural phase in a woman's life that is faced with various physical and psychological changes.  If women do not understand about menopause and are not properly informed, it can lead to excessive worry, and can lead to unpreparedness. The phenomenon was that some women were not ready for menopause, because of the symptoms that appeared which made them uncomfortable. In addition, respondents do not know what they need to prepare when menopause symptoms appear. This community service was carried out on 26 mothers in RT 10, Kaliasin, Kedungdoro Village, Surabaya. The aim of this activity to increasing the readiness of mothers to face menopause.  This activity was carried out by providing health education about menopause, where previously a pretest was given first, then after giving the intervention a posttest was given again. The results obtained before being given health education 14 (54%) respondents felt not ready to face menopause, and 12 (46%) respondents were prepared. After being given health education 21 (81%) respondents were ready to face menopause, and 5 (19%) respondents who felt unprepared. Based on this activity, it was found that there was an increase readiness of mothers to face menopause to help mothers deal with symptoms that appear and improve their quality of life.